Pengaruh Gaya Hidup Konsumtif, Literasi Keuangan dan Toleransi Risiko Terhadap Keputusan Berinvestasi Generasi Z Kecamatan Sukarame Kabupaten Tasikmalaya - Cindi Alwin; Heidi Siddiqa (Journal Economic Management and Business, 2026)
This study bridges the divide between investment aspirations and real-world investment actions among Generation Z residents in Sukarame District, Tasikmalaya. Although many people express intentions to invest, most fail to follow through with execution. The research investigates how consumptive lifestyle patterns, financial knowledge levels, and risk tolerance shape investment choices. Employing a quantitative approach grounded in positivism, it relies on primary data collected through questionnaires from 105 participants selected via purposive sampling. Analysis involved multiple linear regression conducted with SPSS software. Results indicate that consumptive lifestyle, financial literacy, and risk tolerance both jointly and separately demonstrate a positive and significant effect on investment decisions. However, the general standard of investment decision-making remains moderate, highlighting the need to boost financial education and reduce excessive spending tendencies.